2020
DOI: 10.17569/tojqi.671287
|View full text |Cite
|
Sign up to set email alerts
|

Independent Living Needs of Young Adults with Intellectual Disabilities

Abstract: The aim of this study was to determine the independent living needs of young adults with intellectual disability (YAID) in preparing for adulthood and work life. This study was conducted using the phenomenological design, which is one of the qualitative research methods. 10 YAIDs were observed, their skills were evaluated, and semi-structured interviews were conducted with a total of 30 individuals consisting of 10 individuals from each group, with their parents, employers, and teachers regarding the employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A significant number of earlier studies conducted in many countries have shown that teachers have concerns about working with students with disabilities [10]. For example, a recent study conducted in Kenya showed that CWID were not taught effectively because teachers were not trained enough [11]. Other previous studies also showed that teachers lacked confidence for teaching in fully inclusive classrooms due to deficits in specialized skills and knowledge [12] and feel anxious when teaching in classrooms with diverse students [13].…”
Section: Globalmentioning
confidence: 99%
“…A significant number of earlier studies conducted in many countries have shown that teachers have concerns about working with students with disabilities [10]. For example, a recent study conducted in Kenya showed that CWID were not taught effectively because teachers were not trained enough [11]. Other previous studies also showed that teachers lacked confidence for teaching in fully inclusive classrooms due to deficits in specialized skills and knowledge [12] and feel anxious when teaching in classrooms with diverse students [13].…”
Section: Globalmentioning
confidence: 99%
“…Thus, they should acquire skills in a number of key areas to achieve independency. These are: daily-life skills, selfdetermination skills, interpersonal skills, and employment skills [3].…”
Section: Introductionmentioning
confidence: 99%